Impedance‐Enabled Camera‐Free Intrinsic Mechanical Cytometry. Issue 7 (20th May 2022) - Feng, Yongxiang; Chai, Huichao; He, Weihua; Liang, Fei; Cheng, Zhen; Wang, Wenhui
Abstract: Mechanical properties of single cells are important label‐free biomarkers normally measured by expensive and complex imaging systems. To unlock this limit and allow mechanical properties comparable across different measurement platforms, camera‐free intrinsic mechanical cytometry (CFIMC) is proposed for on‐the‐fly measurement of two major intrinsic mechanical parameters, that is, Young's modulus E and fluidity β, of single cells. CFIMC adopts a framework that couples the impedance electrodes with the constriction channel spatially, so that the impedance signals contain the dynamic deformability information of the cell squeezing through the constriction channel. Deformation of the cell is thus extracted from the impedance signals and used to derive the intrinsic mechanical parameters. With reasonably high throughput (>500 cells min −1 ), CFIMC can successfully reveal the mechanical difference in cancer and normal cells (i.e., human breast cell lines MCF‐10A, MCF‐7, and MDA‐MB‐231), living and fixed cells, and pharmacological perturbations of the cytoskeleton. It is further found that 1 µM level concentration of Cytochalasin B may be the threshold for the treated cells to induce a significant cytoskeleton effect reflected by the mechanical parameters. It is envisioned that CFIMC provides an alternative avenue for high‐throughput and real‐time single‐cell intrinsic mechanical analysis. Abstract : In this study, camera‐free intrinsic mechanical cytometry (CFIMC) is proposed for high‐throughput and real‐time single‐cell intrinsic mechanical characterization, taking the characteristics of impedance signals. The strategy of CFIMC adopts a framework that couples the impedance electrodes with the constriction channel spatially, so that the impedance signals contain the dynamic deformability information of the cell squeezing through the constriction channel.